Evaluation of French pressuremeter : progress report no. 7 December 1977 / by Constructed Facilities Division, Department of Civil Engineering, Massachusetts Institute of Technology for U.S. Department of Transportation, Federal Highway Administration. - Massachusetts Institute of Technology. Department of Civil Engineering. Constructed Facilities Division.; Germaine, John T.; Ladd, Charles C. (Charles Cushing); United States. Federal Highway Administration. (Tufts University. Tisch Library., 2019)
1 online resource : illustrations; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.